Poland 1939 the outbreak of World War II - Moorhouse, Roger (Basic Books, 2020)
"For Americans, World War II began in December of 1941, with the bombing of Pearl Harbor; in Soviet historical accounts, the war was prompted by the German invasion of June 1941; for the British and the French, the war was not taken seriously until the German forces penetrated French territory in May 1940. But for Poland, the war began on September 1, 1939 when the Nazi army invaded Poland by land and by air, where they were soon joined by Stalin's army. In Poland 1939, Roger Moorhouse introduces the September Campaign as the triggering event of World War II and challenges the prevailing historical understanding of the start the war. The Polish campaign of 1939 is the least written-about and least understood campaign of World War II. Although many of the doctrines and practices that would feature so strongly throughout the war - the targeting of civilians, race war, Blitzkrieg, aerial bombing - would see their debut in Poland, the campaign is rarely given any real scrutiny. In his close examination of the often-overlooked September Campaign, Moorhouse explores the Anglo-French betrayal of Poland, when both Britain and France pledged to defend Poland but then did nothing of the sort (their inaction resulted in the slaughter of 16,000 Polish civilians). In Poland 1939, Moorhouse offers an insightful account of the September Campaign, and unravels the misconceptions and myths that have clouded the beginnings of World War II. This is the first English-language history of the September Campaign. Moorhouse draws from memoirs of generals, diplomats, letters of soldiers and civilian diaries, as well as private and previously untapped documentary archives in Poland, to expose the true history of the September Campaign, the event that set the tone for the bloody conflict to come."